Gender Issues and Space in Esan Festivals and Ceremonies - Jamgbadi, Esther (International Journal of Language and Literary Studies, 2021)
The paper examines the areas of discrimination against women in Esan cultural activities. It focuses on the spaces in which women are marginalized especially in festivals and cultural ceremonies. To actively demonstrate this sidelined participation of women, the New Yam festival and the Efae ceremony are highlighted. In evaluating the marginal spaces of women, the study adopts the tenets of patriarchy and the feminist theory to see the specific attitudes and instruments of marginalization. It identifies patriarchy, as the major cause of discrimination and also shows that the situation persists till date because women offer no resistance to their plight. The paper intends to incite women to open their eyes to their unpalatable position.